Individual‐ and hospital‐level correlates of red blood cell, platelet, and plasma transfusions among hospitalized children and neonates: a nationally representative study in the United States. Issue 8 (26th June 2020) - Goel, Ruchika; Josephson, Cassandra D.; Patel, Eshan U.; Petersen, Molly R.; Packman, Zoe; Gehrie, Eric; Bloch, Evan M.; Lokhandwala, Parvez; Ness, Paul M.; Katz, Louis; Nellis, Marianne; Karam, Oliver; et al.
Abstract : BACKGROUND: Factors associated with red blood cell (RBC), plasma, and platelet transfusions in hospitalized neonates and children across the United States have not been well characterized. METHODS: Data from the Kids' Inpatient Database (KID) 2016 were analyzed. KID is a random sample of 10% of all uncomplicated in‐hospital births and 80% of remaining pediatric discharges from approximately 4200 US hospitals. Sampling weights were applied to generate nationally representative estimates. Primary outcome was one or more RBC transfusion procedures; plasma and platelet transfusions were assessed as secondary outcomes. Analysis was stratified by age: neonates (NEO; ≤28 d), and nonneonates (PED; >28 d and <18 y). Multivariable logistic regression was used to estimate adjusted odds ratios (aORs) and 95% confidence intervals (95% CIs). RESULTS: Among 5, 604, 984 total hospitalizations, overall prevalence of transfusions was 1.07% (95% CI, 0.94%‐1.22%) for RBCs, 0.17% (95% CIs, 0.15%‐0.21%) for plasma and 0.35% (95% CI, 0.30%‐0.40%) for platelet transfusions. RBC transfusions occurred among 0.43% NEO admissions and 2.63% PED admissions. For NEO admissions, RBC transfusion was positively associated with nonwhite race, longer length of hospitalization, highest risk of mortality (aOR, 86.58; 95% CI, 64.77‐115.73) and urban teaching hospital location. In addition to the above factors, among PED admissions, RBC transfusion was positively associated with older age, female sex (aOR, 1.10; 95% CI, 1.07‐1.13), and elective admission status (aOR, 1.62; 95% CI, 1.46‐1.80). Factors associated with plasma and platelet transfusions were largely similar to those associated with RBC transfusion, except older age groups had lower odds of plasma transfusion among PED admissions. CONCLUSIONS: While there is substantial variability in the proportion of neonates and nonneonatal children transfused nationally, there are several similar, yet unique, nonlaboratory predictors of transfusion identified in these age groups.